Model Parkir Yang Optimal Berdasarkan Analisis Perhitungan Jumlah Kendaraan Di Area Parkir Yang Tersedia - Mekar Ria Pangaribuan (MAJALAH TEKNIK SIMES, 2019)
Abstract Along with the increase in the number of vehicles, the parking area at the north Bengkulu Regency Regen Office has a lack of parking area availability. The research objectives are : a) Knowing how much the needs of parking, and b) Designing the model and parking system that will be applied. The research method is by analyzing the number of vehicles entering the parking location, type of vehicle, how much parking capacity. the result of the study are the design of parking lost of 12.000M2. I entrance and 2 exist the number of vehicles that can be accommodated are 468 two-wheeled vehicle and 39 four-vehicles. With Parking areas as follow: A, C, D, E, G,H, J, K, L, M, N and G are two-wheeled parking (motorcycles). B, F, I, P and Q are four-wheeled parking area (cars). The parking model/patern that can be applied is the 900 angle parking pattern, by accommodating the number of vehicles reaching 350 SRP (the number of projections of addition in the next 5 years).